2019
DOI: 10.1177/1060028019889550
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Use and Outcomes Associated With Glycoprotein-IIb/IIIa Inhibitors in Patients With Acute Coronary Syndromes Undergoing Percutaneous Coronary Intervention

Abstract: Background: Glycoprotein IIb/IIIa inhibitors (GPIs) are a treatment option in the management of acute coronary syndromes (ACSs). Evidence supporting the use of GPIs predates trials establishing the benefits of P2Y12 inhibitors, routine early invasive therapy, and thrombectomy devices in patients with ACS. Objective: The aim of this study was to determine trends in GPI use and their associated outcomes in contemporary practice. Methods: We assessed GPI use in patients with ACS undergoing percutaneous coronary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Historically, these patients have been routinely treated with glycoprotein IIb/IIIa receptor inhibitors (GPI), based on their potent and fast-acting antiplatelet effect, which has been shown to reduce mortality in patients at high risk of thrombotic complications [ 4 ]. More recently, the results of some randomized controlled trials [ 5 , 6 ], the growing awareness of the increased hemorrhagic risk associated with these drugs [ 7 ], and the availability of potent, fast-acting oral antiplatelet agents [ 8 , 9 ] questioned and reduced their use in clinical practice [ 10 ]. Nevertheless, optimal levels of platelet inhibition during pPCI are unfrequently achieved after loading dose of either prasugrel or ticagrelor [ 11 , 12 ], whereas the use of high-dose tirofiban on top of a loading dose of 600 mg clopidogrel was associated with improved myocardial reperfusion in the absence of increased bleedings in the On-TIME 2 trial [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, these patients have been routinely treated with glycoprotein IIb/IIIa receptor inhibitors (GPI), based on their potent and fast-acting antiplatelet effect, which has been shown to reduce mortality in patients at high risk of thrombotic complications [ 4 ]. More recently, the results of some randomized controlled trials [ 5 , 6 ], the growing awareness of the increased hemorrhagic risk associated with these drugs [ 7 ], and the availability of potent, fast-acting oral antiplatelet agents [ 8 , 9 ] questioned and reduced their use in clinical practice [ 10 ]. Nevertheless, optimal levels of platelet inhibition during pPCI are unfrequently achieved after loading dose of either prasugrel or ticagrelor [ 11 , 12 ], whereas the use of high-dose tirofiban on top of a loading dose of 600 mg clopidogrel was associated with improved myocardial reperfusion in the absence of increased bleedings in the On-TIME 2 trial [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the patients were prescribed clopidogrel for at least nine months according to the protocol, and the introduction of prasugrel and ticagrelor happened midway through the study period, we were unable to compare different P2Y12 inhibitors or durations of DAPT in this analysis. Finally, current PCI procedural techniques have some important differences from 2008-11, including lower use of glycoprotein IIb/IIIa Inhibitors, and higher frequency of radial access site, resulting in a lower risk of bleeding [35,36].…”
Section: Weaknessesmentioning
confidence: 99%
“…Bleedings negatively impact prognosis in acute coronary syndromes [3]; therefore, several bleeding avoidance strategies, including radial access, femoral vascular closure devices (VCD), and safer antithrombotic drugs, such as bivalirudin, have been adopted in order to improve outcomes [4]. Consequently, the use of potent antiplatelet agents known to increase hemorrhagic risk, such as Gp IIb/ IIIa inhibitors (GPI) [5], has declined in recent years [6] and is now mostly recommended for bail-out by clinical practice guidelines [7]. is change in practice is reflected in randomized trials comparing radial and femoral access, with variable reported rate of GPI use (generally higher in previous trials and lower in contemporary trials).…”
Section: Introductionmentioning
confidence: 99%